Amino Acid Substitutions in Putative Selectivity Filter Regions III and IV in KdpA Alter Ion Selectivity of the KdpFABC Complex from Escherichia coli - Bertrand, Jessica (American Society for Microbiology, 2004)
When grown under conditions of potassium limitation or high osmolality, Escherichia coli synthesizes the K(+)-translocating KdpFABC complex. The KdpA subunit, which has sequence homology to potassium channels of the KcsA type, has been shown to be important for potassium binding and transport. Replacement of the glycine residues in KdpA at positions 345 and 470, members of putative selectivity filter regions III and IV, alters the ion selectivity of the KdpFABC complex.